Ethnomedicinal Plants of Malwa Region of Madhya Pradesh and Rajasthan - Jadhav, Dinesh (Indian Forester, 2022)
An attempt has been made to prepare a detailed account of ethnomedicinal plants of Malwa region of Madhya Pradesh and Rajasthan. The paper deals with the 172 species of probable ethnomedicinal potential, belonging to 150 genera and 74 families from Malwa region of Madhya Pradesh and Rajasthan. These taxa are used for curing various ailments among the different ethnic societies. For each species the information regarding botanical names, family, local names, parts used and ethnomedicinal uses have been provided. The information has been gathered by field survey and from available literature.